An investigation into the prediction of thermal and stress distributions set up during welding using finite-element analysis - Kesler, David Jonathan (Department of Civil Engineering, 2016)
During the welding process, thermal and stress distributions are set up in the workpiece. These thermal stresses are recognized as among the most important factors affecting the weldability of steels, producing distortion and cracking in weldments. This thesis examines the history and theory of the welding process, including the mathematical and finite-element theory of heat conduction. Using simple models, the finite-element method is also compared with theoretical Fourier analysis solutions. In addition, a complex: two-dimensional finite-element thermal and stress analysis of the welding process is performed, in which a thermo-elasticplastic finite-element model is used to predict the longitudinal welding stresses perpendicular to the weld. In this model, the weld is represented simply as a high temperature load acting at a predetermined position for a particular time interval. The metallurgical phase transformations and work hardening effects are ignored. The predictions from the finite-element analysis are then compared with experimental data obtained from a welding test.